Pengembangan Instrumen Tes Literasi Sains Berdasarkan Framework PISA 2025 untuk Siswa SMA - Maya Mustika; Fatchiyatun Ni’mah; Ennike Gusti Rahmi; Saulim DT Hutahaean (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The achievement of Indonesian students' scientific literacy in PISA is still low, requiring the development of valid and contextual assessment instruments. This study aims to develop a scientific literacy instrument based on the PISA 2025 Framework with the unique use of the local context of Kalimantan for high school students that is valid and reliable in the subjects of Physics, Chemistry, and Biology. The research method uses a Research and Development (R&D) approach with an adapted 4D development model (Define, Design, Develop, Dissemination). In this study, the implementation of the 4D development model only reaches the development stage. The results of the instrument validation test by 3 validators showed an average score of 3.72 with a very good category. The instrument trial involved 241 grade 10th and 11th high school students in Palangka Raya. The empirical test results produced 18 valid physics questions with a reliability value of 0.784 (high), 19 valid chemistry questions with a reliability value of 0.814 (very high), and 15 valid biology questions with a reliability value of 0.735 (high). Thus, the scientific literacy instrument developed based on the PISA 2025 Framework has proven valid and reliable for measuring students' scientific competencies. This instrument can be used by teachers as a formative assessment tool in the classroom, a reference for developing contextual science questions aligned with international standards for high school students, and is expected to improve Indonesian students' scientific literacy achievements in accordance with PISA standards.